Reproducibility of incremental maximal cycle ergometer tests in healthy recreationally active subjects. (16th September 2015) - Dideriksen, Kasper; Mikkelsen, Ulla Ramer
Summary: Purpose: Testing of the ventilatory threshold (VT) and maximal oxygen uptake (VO2 peak) is relevant for the evaluation of a range of training studies, clinical trials and cross‐sectional studies. Due to a possible learning effect, a familiarization test is often performed to increase test reproducibility. However, limited research has investigated this learning effect and reproducibility of maximal exercise testing. The most appropriate ways to determine VT and VO2 peak are not clear, and this study evaluated two approaches (V‐slope and a combined method) for the determination of VT and five time‐averaging intervals (60, 30, 15, 10 and 5 s) for the determination of VO2 peak to compare test results and reproducibility. Methods: Thirteen recreational triathletes completed three identical incremental maximal cycle ergometer tests. The initial workload was 75 and 100 watt (W) for women and men, respectively, and the workload was increased by 4 W/10 s thereafter. No familiarization test was performed. Results: VO2 peak increased significantly as the time‐averaging interval became shorter (e.g. 5‐s interval 48·7 versus 60‐s interval 44·8 ml O2  kg −1  min −1 ; overall P <0·001). All test results were similar for the three test rounds, indicating that repeated testing was not associated with any learning effect. The different VT measuring methods (CV 7·6 versus 7·7%, P  = 0·58) and VO2 peak time‐averaging intervals (CV 3·7–4·4%, P  = 0·99) did not influence test reliability. Conclusions: The reproducibility of VT and VO2 peak was not affected by measuring methods and time‐averaging intervals. However, the time‐averaging intervals significantly affect the absolute VO2 peak values. Furthermore, no learning effect of maximal cycle ergometer testing was observed.